Treatment of posterior gastric wall gastrointestinal stromal tumor with gastric sleeve: A case report - Navarini, Daniel; Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; Rohden, Thiago Beltrame; Reffatti, Diego; de Oliveira, André Emanuel Lunkes; Naher, Christopher; Baldus, Felipe; de Lima, Lais Antunes; de Moura, Virgínia de Carli; et al. (Clinical and Biomedical Research, 2018)
Gastrointestinal stromal tumors (GISTs) are the most common non-epithelial tumors of the gastrointestinal tract1. The most usual location is the stomach, followed by the small intestine, where it may cause digestive bleeding and anemia6. Surgical resection of the tumor is the gold standard treatment, and definitive diagnosis is based on immunohistochemical analysis of the surgical specimen8. We report the case of a 53-year-old man with gastric GIST presenting with endophytic and exophytic growth, located at the posterior wall of the stomach, in the antrum-body transitional zone, treated with gastric sleeve. Keywords: Gastrointestinal stromal tumors; gastrointestinal neoplasms; gastric sleeve; diagnosis; prognosis; treatment